Changes on Hepatitis C virus genotype distribution in Western Turkey: Evaluation of twelve-year data - Çetin Duran, Alev; Kaya Çetinkaya, Özgül; Sayıner, Ayça Arzu; Şeydaoğlu, Gülşah; Özkarataş, Emre; Abacıoğlu, Hakan (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Hepatitis C virus (HCV) prevalence is 1% in Turkey with genotype 1 being the predominant type traditionally. However unique geographical location of Turkey and increasing human migration in the region influences the epidemiology of the infection. The aim of this study was to determine the changes in distribution of HCV genotypes and risk factors.Materials and Methods: In this retrospective single-center study, HCV genotyping results of 558 patients were evaluated in between 2005 and 2016.Three different HCV genotyping assays were used during the 12-year study period;restriction fragment length polymorphism (RFLP), Abbott Real Time HCV Genotype II and Bosphore HCV genotyping kit.Results: The most prevalent HCV genotype was genotype 1 detected in 88.4% of the patients followed by genotype 3 (5.2%),genotype 4 (2.9%),genotype 2 (2.1%), mixed genotypes (1.1%) and genotype 5 (0.3%).Genotype 1a showed an increasing prevalence.There were 19 patients (3.4%) either of foreign nationalities or Turkish citizens living abroad. Genotype 3 was the most common type among these patients which 10.3% had intravenous drug use history.Syrian migrant population differed in terms of HCV genotypes.Genotype 5 detected in two Syrian patients, which is the first report of HCV type 5 in Western Turkey. Among the HCV genotype 4 infected patients, 31.3% were Syrians.Conclusion: Our study showed that although genotype 1b dominance continues, the distribution and prevalence of HCV genotypes are changing in our region mainly due to migration and increase in the frequency of patients with non-traditional risk factors such as intravenous drug use. Monitoring the epidemiology of HCV genotypes may provide guidance in treatment decisions.